ROMANIAN RURAL AREAS TODAY: FROM UNDERPERFORMANCE TOWARDS SUSTAINABLE DEVELOPMENT - Stanef Mihaela, Roberta; Chenic Alina, Stefania; Manole Alina, Magdalena (Economics of Agriculture, 2012)
EU cohesion policy measures aim to overcome interregional disparities and strengthen backward regions, while rural development policy should contribute to the better standard of life of rural inhabitants To achieve synergy between these policies (and many others), a stronger linkage is needed between the development strategies of regions and the strategies of development formulated by component localities Competitiveness has become a key term in economic theory in general, and in the EU in particular. The problem of the sustainable development of the rural areas constitutes a high priority for Romania as a new member of the European Union This can be entailed by implementing a coherent strategy that can realize a balance between the need to preserve the economic, ecologic and socio-cultural area on one hand, and the tendency of country life modernization, on the other side. Although the Romanian rural area hosts a rich culture with a strong traditional character, with regional differences, this cannot fully put into value its resources, and a paradoxical scarcity is maintained, due to the lack of attractiveness and promotion of rural areas